Identifying the Factors Affecting Internet Memes to Become Viral on Social Media - Md Nawawi, Elly Atiqah; Izzudin, Muhammad Faiz; Mohd Zulkafli, Nur Atiqah; Januri, Siti Sarah (2020)
Memes is a post that social network user usually post in social network to convey messages, feeling or opinion in sarcastic ways. The tendency of people using memes nowadays should be exploited by the people in good and more useful ways. The aim of the study is to examine the factors contributing to the largest number of internet memes shares or its virality. The data of the study is obtained from a famous Malaysian Facebook named ‘Gag Malaysia’. Negative Binomial Regression was used to find the factors that affects the number of shares. In the Negative Binomial Regression analysis indicates that all variables are significant except for the main effect of Types of Memes and Self-enhancing, the main effect of day of posting and Weekdays and the Number of Comments.